Influence of preliminary irradiation on radiation hardness of silicon and indium antimonide - Litovchenko, P.G.; Wahl, W.; Groza, A.A.; Dolgolenko, A.P.; Karpenko, A.Ya.; Khivrych, V.I.; Litovchenko, O.P.; Lastovetsky, V.F.; Sugakov1, V.I.; Dubovy, V.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Radiation hardness of semiconductor detectors based on silicon is, first of all, determined by an introduction rate of point defects and aggregation of defect clusters. So introduction of electrically inactive impurity of oxygen promotes taking a vacancy stream aside from a doping impurity of phosphorus. Thus, in spite of the greater capture radius of vacancies by phosphorus atoms, high concentration of oxygen will suppress formation of E-centres. Use of neutron transmutation doping method allows to receive silicon with enhanced radiation hardness. The preliminary irradiation with neutrons or charged particles with subsequent annealing also allows to increase radiation hardness of material. It is due to introduction into the volume of material some additional sinks for primary radiation defects that causes enhanced radiation hardness of such material.